Contribution to the lichen flora of Gürgen Daǧi (Çanakkale) - (:unkn) unknown (My University, 2006)
A list of 75 lichen taxa is reported from Gürgendaǧι Mountain located to the north of Kazdaǧι (Ida Mountain), in Çanakkale province. Among the identified taxa, 41 taxa are epiphytic, 26 saxicolous and 8 terricolous. All of the taxa are new records for the area. Nineteen taxa are new for the province. © TÜBİTAK.
Keywords: Çanakkale; Flora; Gürgen Daǧi; Lichen